Disability in Community-Dwelling Older Adults: Exploring the Role of Stroke and Dementia - Brian J. Stamm; James F. Burke; Chun Chieh Lin; Rory J. Price; Lesli E Skolarus (SAGE Publishing, 2019)
Objectives: We sought to determine the relative contributions of stroke, dementia, and their combination to disability and racial differences in disability among community-dwelling older adults. Methods: We performed a cross-sectional study of 6848 community-dwelling older adults. We evaluated the associations of stroke, dementia, and their combination with activities of daily living (ADL) limitations (range 0-7). We then explored the impact of stroke and dementia on race differences in ADL limitations using Poisson regression after accounting for sociodemographics and comorbidities. Results: After full adjustment, ADL limitations differed among older adults with stroke and dementia. Older adults without stroke or dementia had 0.32 (95% CI 0.29-0.35) ADL limitations compared to 0.64 (95% CI 0.54-0.73) with stroke, 1.36 (95% CI 1.20-1.53) with dementia and 1.84 (95% CI 1.54-2.15) with stroke and dementia. Overall, blacks had 0.27 (95%CI 0.19-0.36) more ADL limitations than whites. Models accounting for stroke led to a 3.7% (95%CI 2.98%-4.43%) reduction in race differences, while those for dementia led to a 29.26% (95%CI 28.53%-29.99%) reduction and the stroke-dementia combination −1.48% (95%CI −2.21% to −0.76) had little impact. Discussion: Older adults with stroke and dementia have greater disability than older adults with either of these conditions alone. However, the amount of disability experienced by older adults with stroke and dementia is less than the sum of the contributions from stroke and dementia. Dementia is likely a key contributor to race differences in disability.